Consumer Demand on Halal Cosmetics and Personal Care Products in Indonesia - Muniaty Aisyah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This research aims to analyze the influential factors involved in Moslem consumers’ decision to purchase halal cosmetics and personal care products in Indonesia by using the Theory of Planned Behavior. 100 questionnaires were analyzed using Structural Equation Modeling, collected from respondents of female consumers who purchased Wardah cosmetics and personal care products in South Jakarta and South Tangerang. The findings show that attitude, subjective norm, perceived behavioral control and purchase intention are positively related to the consumers’ decision to purchase halal cosmetics and personal care products. By addressing the consumers’ traits that can predict halal cosmetics and personal care products necessity, marketers could generate proper marketing strategies to validate consumers’ demand which in turn will stimulate the growth of halal products industry in Indonesia.DOI: 10.15408/aiq.v9i1.1867